Integrating Digital Personalised Learning into Early-Grade Classroom Practice: A Teacher–Researcher Design-Based Research Partnership in Kenya - Rebecca Daltry; Jessica Hinks; Chen Sun; Louis Major; Mary Otieno; Kevin Otieno (Education Sciences)
Although growing evidence suggests that digital personalised learning (DPL) has the potential to enhance learning outcomes, there is little research about the effective implementation and integration of DPL into the classroom. The aim of this study is to investigate the pedagogical implications of integrating a DPL tool into Kenyan early-grade classrooms to bridge the gap between theory and practice. This paper reports on systematic, design-based research conducted over three years, featuring five phases, each testing iterations to specific aspects of DPL implementation. The findings demonstrate that the pedagogic dimensions of classroom-integrated DPL are pivotal to its effective uptake and implementation. A key research contribution is the identification of a distinct gap between theoretical and practical conceptualisations of DPL, with teachers focused primarily on curriculum alignment and classroom management. The analysis also identified teachers’ central role in the process of personalisation, nuancing existing DPL frameworks by exploring interactions between the digital and classroom environments, as well as highlighting important considerations around access and equality. Recommendations include the co-design of DPL with teachers, drawing on their pedagogical perspectives to enhance integrative approaches.